Designing the Future: Exploring the Smart Manufacturing Ecosystem and Future Landscape - Bouguern, Siham (Journal of Novel Engineering Science and Technology, 2024)
The manufacturing industry has continuously evolved alongside technological advancements, progressing from steam engines to electricity, microprocessors, computers, automation, and most recently, artificial intelligence, the Internet of Things (IoT), and cyber-physical systems. This digital transformation has ushered in the era of smart manufacturing, characterized by the development of intelligent systems. In this paper, we provide a comprehensive exploration of the smart manufacturing ecosystem, assessing its current status and forecasting future trends. Key elements and technologies central to smart manufacturing and Industry 4.0 (I4.0) encompass digital manufacturing, big data analytics, cloud manufacturing, digital twins, IoTs, and smart factories. Our research adopts a qualitative approach, offering a broad perspective on the concept of smart manufacturing. This paper aims to explore these emerging trends and shed light on future opportunities associated with this digital transformation. Consequently, enterprises need to redesign their businesses and models to achieve the benefits disclosed by these new settings.